(untitled) (Studia theodisca, 2023)
The essay analyses the characterisation of power in Christoph Ransmayr’s novel Cox oder Der Lauf der Zeit. Specifically, power is analysed on its political level, with the social implications that it necessarily entails on both the human and personal level, showing the individual in charge locked in the solitude of his distance from others; and on its gender level, which is expressed in the novel by the subjugation of the female to the male. In conclusion, nature and time in the novel are highlighted in their function as obstacles to limitless power.